Evaluation of burnout syndrome in teachers of the National Institute of Youth and Sports (NIYS) - Mbame, Jean-pierre; Ephrem, Menkes; Lamou, Bonoy; Evariste Edmundo, Djomo Ngnoko (مجلة دراسات في سيكولوجية الانحراف, 2022)
The objective of this study is to determine the prevalence of burnout and to identify the socio-demographic and professional factors that influence burnout among INJS teachers. Methodology: A study using a self-administered questionnaire made it possible to collect the data. SPSS version 20.0 software allowed us to analyze the data. Results: The prevalence of burnout was 68.85%. It is noted that 11.8% of the variance in emotional exhaustion was explained by seniority in the establishment and age; 13.3% of the variance in depersonalization is explained by seniority in the establishment and the number of children in charge; Finally 10.5% of the variance in loss of personal achievement is explained by marital status. Conclusion: This study shows that burnout among NIYS teachers is a reality. Age, marital status, number of children in care and seniority in the establishment have a significant influence on burnout